The Effect Of Nursing Supervision, Competence, And Work Motivation On Nurse Performance At EMC Sentul Hospital - Sari, Puji Swastika; Madiistriyatno, Harries; Hasudungan, Eddy Hermawan (SEAN Institute, 2024)
The author's aim in this research is to find out how much influence nursing supervision, competence and work motivation have on the performance of nurses at EMC Sentul Hospital. This type of research uses a quantitative approach with correlation regression analysis, so that an overview of the variables is obtained which then tests the hypothesis regarding this influence. The sampling technique used in this research uses the Slovin formula and the analysis technique used is linear regression using the SPSS 25.0 application. The results obtained were that nurse competency had the most influence on nurse performance, while nursing supervision and motivation had a smaller influence on performance. From this research, the competency of nurses themselves needs to be maintained, but it is the supervision and motivation of nurses that must be improved so that performance increases will be more optimal. The implementation of nursing supervision, supervision of nurse competency, and synergistic increase in nurse work motivation must be improved to increase nurse work motivation.